Value-based Islamic education management: Developing leadership and commitment in contemporary Islamic school environments - Astuti, Astuti (Edelweiss Applied Science and Technology, 2024)
This study investigates the impact of integrating local values into Islamic education management on student leadership and commitment in South Sulawesi, employing a mixed-methods approach. Purpose: The research aims to understand how embedding local values such as sipakatau and siri na pacce influences student development in Islamic schools. Design/Methodology/Approach: A combination of quantitative and qualitative methods was used. Quantitative data were collected through structured questionnaires distributed to students, teachers, and school administrators. Qualitative insights were obtained from interviews with stakeholders at Madrasah Aliyah Negeri (MAN) 1 Makassar, Madrasah Aliyah Negeri (MAN) 2 Bone, Madrasah Aliyah Al-Mujahidin Gowa, and Sekolah Islam Terpadu (SIT) Al-Ihsan Makassar. Findings: The quantitative results show that 42% of respondents strongly agree on the effective implementation of local values, positively impacting student leadership and commitment, with the highest support from school administrators. Qualitative data corroborated these findings, highlighting that local values significantly enhance character development and leadership skills. Conclusion: The integration of local values into educational management positively affects student leadership and commitment, offering novel empirical evidence in this area. Practical Implications: Policymakers should embed local values into educational policies and curricula, and provide training for educators to implement these values effectively. Limitations: The study’s limitations include potential response bias and regional specificity. Future Research: Further studies should explore diverse educational contexts and employ longitudinal designs to assess the long-term impacts of local values on educational outcomes.